PSXIII-35 Administration of prostaglandin F2α 24 h prior to CIDR removal alters distribution of estrus expression in replacement beef heifers assigned to the Select-Synch estrus synchronization protocol. - Fontes, P (J Anim Sci, 2018)
This experiment evaluated the effects of the administration of prostaglandin (PG) F2α 24 h prior to CIDR removal on the distribution of estrus and pregnancy rates to AI in beef heifers. A total of 305 Bos indicus-influenced heifers were assigned to the 7-d Select-Synch+CIDR estrus synchronization protocol. On d 0, heifers received 100 µg of GnRH and a CIDR device containing 1.38 g of progesterone, and were randomly assigned to 1 of 2 treatments: 1) PG6 (n=155), heifers received a 500-µg injection of PGF2α on d 6; or 2) CONTROL (n=150), heifers received a 500-µg injection of PGF2α on d 7. Heifers were monitored for estrus activity twice daily for 84 h after CIDR removal. Heifers were artificially inseminated 12 h after being detected in estrus. Heifers that were not in estrus by 84 h after CIDR removal received a second 100-µg injection of GnRH and were artificially inseminated 12 h later. Pregnancy was diagnosed 35 d after AI via circulating concentrations of pregnancy-associated glycoproteins. There was no effect of treatment (P=0.59) on overall incidence of estrus (86.8 and 84.4% for PG6 and CONTROL, SEM=6.0). Cumulative incidence of estrus was greater (P<0.01) for heifers receiving PG6 by 48 (70.5 vs 54.5%; SEM=6.6) and 60 h (78.9 vs 68.5%; SEM=6.6) after CIDR removal. Non-cumulative incidence of estrus was also greater (P<0.01) for PG6 heifers at 48 h (63.6 vs 51.3%; SEM=2.4). In turn, incidence of estrus was increased (P<0.09) in CONTROL heifers at 60 h (14.0 and 8.4%; SEM=2.4) and 72 h (15.3 vs. 5.8%, SEM=2.4). No differences in pregnancy rates were detected (P=0.43) between treatments (64.2 vs 59.8%, respectively; SEM=4.7). In conclusion, earlier administration of PGF2α altered the distribution of estrus in beef heifers, resulting in an increased proportion of heifers exhibiting estrus within 60 h after CIDR removal